Diffusion of information and communication technologies: a takeoff analysis. (6th May 2010) - Rajagopalan, Balaji; Hillison, Derek; Calantone, Roger; Sambamurthy, Vallabh
In an increasingly global economy, Information and Communication Technologies (ICTs) are critical for nations to participate in trade and reap the benefits of access to world markets. Economists call for investments in technologies that enable innovations and spur economic development in the country. In addition to being the source of innovation, economic growth also depends on the ability of nations to absorb and apply new innovations that germinated elsewhere. Despite accumulating evidence that several factors play an important role in the assimilation of new technologies, the drivers of the adoption of digital technologies are not well understood and the findings remain inconsistent. Based on theories of economic growth and innovation diffusion theory, and using the well-known takeoff phenomenon as the underpinning, we hypothesise and empirically examine the relationships between human capital (literacy, life expectancy), cost, international trade (foreign direct investment), communications infrastructure (television and telephone) and the takeoff of digital technologies. Our findings confirm that important differences exist among the high-, medium- and low-income countries with respect to the takeoff times for ICT. In addition, our study reveals the differential impact of the factors on takeoff for the three income groups. Policy implications include the need for tailoring the adoption programmes based on country income group, technology type and adoption stage (before or after takeoff).